Perbedaan Kegiatan Penghuni di Ruang Makan dengan Ruangan lain berdasarkan ketersediaan Ruang Makan pada Hunian - Putri, Sarah Heriyanti; Pamela, Sofia; Kusuma, Hanson Endra; Riska, Annisa Safira (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2021)
The existence of a dining room is now rarely found in some residences. Some people who do not have a dining room will be forced to use a room to carry out eating activities. In comparison, other people use the dining room to do other activities. It shows that the existence of space reflects the behaviour of the occupants in living. This study will compare community activities with residential conditions with a dining room and those without a dining room. This study aims to reveal the differences and activities most often carried out in the two conditions. Then all these activities will be classified based on the theory of affordance. This research method uses a sequential mixed-method approach by distributing online questionnaires. The data collected were analyzed using principal component analysis and analysis of the mean latent variables to find the most dominant variable. Based on the study results, the most dominant activity carried out in residential areas that have a dining room is only eating activities. Meanwhile, residential areas that do not have a dining room include learning, working, relaxing and household activities.Â